Utilization of Free Soft Tissue Grafts in Otoplasty: A Simple Yet Effective Way to Avoid Suture Extrusion. (9th April 2022) - Alzayadneh, Islam; Glikson, Eran; Shapiro, Jordan; Rival, Ella; Solomon, Zachary; Solomon, Philip
Abstract: Background: Prominent ear deformity occurs in 5% of the general population and has been treated by otoplasty for many years to address the psychosocial challenges of having such a deformity. There is extensive literature but no consensus on the best method to address potential surgical complications, including suture extrusion. Objectives: The aim of this article was to describe a surgical technique designed to reduce suture extrusion following otoplasty surgery by placing free soft tissue grafts between Mustardé sutures and postauricular skin. Methods: Two hundred and eleven patients who underwent otoplasties with soft tissue grafts between January 2017 and January 2020 were included in this study. All surgeries were performed by 2 facial plastic surgeons with more than 20 years of experience each, practicing in Toronto, Canada. Patients were followed up to assess for suture extrusion between 12 and 36 months (median, 21 months) postoperatively. The rates of suture complications and extrusion were compared with those previously reported in the literature. Results: Only 2 patients out of 211 (0.47%) had unilateral suture extrusion and were treated with suture removal. This is dramatically lower than the upper values reported in the literature, which average 5.55% (range, 0%-22.2%). Conclusions: A soft tissue graft separating the Mustardé sutures and postauricular skin acts as a barrier, and can be used in conjunction with traditional surgical techniques. By adding this graft in the proposed manner, there is additional tissue reinforcing the suture repair, thereby reducing the rates of suture complications and extrusion without increasing the operative time. Level of Evidence: 4: